Influence of inhomogeneous porosity on effusion cooling - Huang, G; He, L (Elsevier, 2019)
Effusion cooling is an effective cooling technology which is considered as the next logical step of the cooling technology for gas turbine blades. Additive manufacturing technology makes it possible to fabricate effusion cooling structures in gas turbine blades with the optimal parameters and a low cost. However, the sizes of cooling holes were usually inhomogeneous owing to the limited accuracies of additive manufacturing technology. This study investigated the influence of inhomogeneous porosity on effusion cooling. The results showed that the inhomogeneous porosity dramatically affected the cooling effects of the surface film and the internal holes. However, the inhomogeneous porosity had a very slight effect on both global and local effusion cooling efficiency (less than 1%) even when the non-uniformity reached 20%. The intensive heat conduction inside the solid matrix played an important role for eliminating the adverse influence of the inhomogeneous porosity. Higher thermal conductivity, thicker thickness or narrower holes spacing both resulted in a smaller heat resistance and hence enhanced the heat conduction effect. However, the inhomogeneous porosity had a remarkable effect on effusion cooling efficiency when a low-thermal-conductivity Thermal Barrier Coating (TBC) covered the surface. Decreasing the thermal conductivity of TBC would further aggravate the inhomogeneous problem.